Diagnostic role of aortic valve calcium scoring in various etiologies of aortic stenosis - Wisarut Wanchaitanawong; Rungsrit Kanjanavanit; Tanop Srisuwan; Wanwarang Wongcharoen; Arintaya Phrommintikul (Scientific Reports, 2023)
Abstract Most of the studies about aortic valve calcium (AVC) score in aortic stenosis (AS) were based on degenerative or bicuspid AS but not rheumatic AS. We aimed to study the diagnostic accuracy of AVC score to determine severe AS in various etiologies. Adult patients diagnosed with mild to severe AS were enrolled. AVC score were identified from multi-detector computed tomography (MDCT) scan. The AVC score was highest in bicuspid AS (3211.9 (IQR (1100.0–4562.4) AU) compared to degenerative AS (1803.7 (IQR (1073.6–2550.6) AU)), and rheumatic AS (875.6 (IQR 453.3–1594.0) AU), p < 0.001. For the ROC curve to identify severe AS, the AVC score performed well in degenerative and bicuspid AS with the area under the ROC curve (AuROC) 0.834 (95% CI, 0.730, 0.938) in degenerative group; and 0.820 (95% CI, 0.687, 0.953) in bicuspid AS. Whereas AVC score had non-significant diagnostic accuracy with AuROC 0.667 (95% CI, 0.357, 0.976) for male and 0.60(95% CI, 0.243, 0.957) for female in rheumatic AS. The cut-off AVC score values to identify severe AS were AVCS > 2028.9AU (male) and > 1082.5AU (female) for degenerative AS, and > 2431.8AU (male) and > 1293.5AU (female) for bicuspid AS. In conclusions, AVC score is the accurate test for assessing severity in patients with degenerative and bicuspid AS but performs poorly in rheumatic AS group.